Production of Highly Active Extracellular Amylase and Cellulase From Bacillus subtilis ZIM3 and a Recombinant Strain With a Potential Application in Tobacco Fermentation - Dai, Jingcheng; Dong, Aijun; Xiong, Guoxi; Liu, Yaqi; Hossain, Md. Shahdat; Liu, Shuangyuan; Gao, Na; Li, Shuyang; Wang, Jing; Qiu, Dongru (Frontiers in Microbiology, 2020)
In this study, a series of bacteria capable of degrading starch and cellulose were isolated from the aging flue-cured tobacco leaves. Remarkably, there was a thermophilic bacterium Bacillus subtilis ZIM3 which can simultaneously degrade both starch and cellulose at a wide range of temperature and pH values. Genome sequencing, comparative genomics analyses and enzymatic activity assays showed that the ZIM3 strain expressed a variety of highly active plant biomass-degrading enzymes, such as the amylase AmyE1 and cellulase CelE1. The in vitro and PhoA-fusion assays indicated that these enzymes degrading complex plant biomass into fermentable sugars were secreted into ambient environment to function. Besides, the amylase and cellulase activities were further increased by 3-5 folds by using overexpression. Furthermore, a fermentation strategy was developed and the biodegradation efficiency of the starch and cellulose in the tobacco leaves were improved by 30-48%. These results reveal that B. subtilis ZIM3 and the recombinant strain exhibited high amylase and cellulase activities for efficient biodegradation of starch and cellulose in tobacco and could potentially be applied for industrial tobacco fermentation.